Curiosity and creative characters: The impact on students' numerical ability - Rahmawati, Yasinta; Pradana, Kenny Candra; Novalia, Novalia; Rinaldi, Achi; Syazali, Muhamad (Universitas Islam Negeri Raden Intan Lampung, 2021)
The study aims to determine the numerical ability improvement in terms of curiosity and creative character education. The study employs the descriptive quantitative method with survey techniques. The cluster random sampling technique selected 120 students from SMP Islam El-Syihab and MTSN 1 Bandar Lampung. Three classes were chosen from each school which consisted of the seventh, eighth, and ninth grades. Each class consisted of twenty students as the respondents. The analysis technique used was the multiple linear regression to investigate the effect of curiosity and creative characters on students' numerical abilities. The results showed that the curiosity character had a more significant influence on students’ numerical abilities (0.870 or 87%) than the creative character (0,294 or 29%).